Jewish ethnic identity and relations in Hellenistic Egypt : with walls of iron? - Moore, Stewart Alden. (Supplements to the Journal for the Study of Judaism, 2015)
In Jewish Ethnic Identity and Relations in Hellenistic Egypt , Stewart Moore investigates the foundations of common assumptions about ethnicity. To maintain one's identity in a strange land, was it always necessary to band tightly together with one's coethnics? Sociologists and anthropologists who study ethnicity have given us a much wider view of the possible strategies of ethnic maintenance and interaction. The most important facet of Jewish ethnicity in Egypt which emerges from this study is the interaction over the Jewish-Egyptian boundary. Previous scholarship has assumed that this border was a Siegfried Line marked by mutual contempt. Yet Jews, Egyptians and also Greeks interacted in complicated ways in Ptolemaic Egypt, with positive relationships being at least as numerous as negative ones.